Importance-Performance Analysis (IPA) of the Service Quality Dimensions at Poli Tour & Travel - Cahyo, Enggar Dwi; Astriyantika, Meyliana; Kartika , Ni Made Ayu Windu; Siregar, Damara Saputra (Politeknik Negeri Bengkalis, 2024)
This research was conducted at Politour & Travel, headquartered in Bandar Lampung, Lampung Province. Thepurpose of this article is to discuss the assessment of tourism products offered by Politour & Travel as well as the level ofservice quality provided to tourists, based on their expectations and the reality observed in the field. The study wasconducted on 17 respondents who were considered representatives of institutions that have previously used Politour &Travel tour packages. This study uses the Importance Performance Analysis (IPA) approach. The service quality at Politour& Travel is grouped into 5 attributes: Tangibles, Empathy, Responsiveness, Reliability, and Assurance. These 5 attributesare further divided into 23 aspects overall. Then, the average score for each service attribute is plotted on an IPA graph,which consists of four priority quadrants based on importance and performance levels. The main results indicate that theattributes show there are 5 aspects that should be prioritized for service improvement and 9 aspects that need to bemaintained in terms of service quality, as they are deemed satisfactory by consumers who have used Politour & Travelservices.